Social movements, intellectual activism and local struggles: conversation with Arturo Escobar - Culturales Latinoamericanos de la Universidad Andina Simón Bolívar, Sede Ecuador, Estudiantes del doctorado en Estudios (2016)
This conversation was part of a video-conference between professors and students of the doctorate in Latin American Cultural Studies of the Universidad Andina Simón Bolívar- Ecuador and Arturo Escobar, on September 13, 2006, within the framework of discussion raised in the seminar on movements social titled: Collective Insurgencies in Historical-World perspective.